2014
DOI: 10.1097/id.0000000000000021
|View full text |Cite
|
Sign up to set email alerts
|

Influence of an Antidiabetic Drug on Biomechanical and Histological Parameters Around Implants in Type 2 Diabetic Rats

Abstract: Despite controlling blood glucose, voglibose was unable to reverse the bone metabolic effects of DM.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
14
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(15 citation statements)
references
References 40 publications
1
14
0
Order By: Relevance
“…A more recent study utilizing the GK rat model of T2D found that treatment with voglibose, one of the newest α‐GI drugs (approved for use in Asia), was insufficient to reverse the negative effects of diabetes on osteo‐integration of dental implants . From this study, the authors inferred a detrimental effect of α‐GI treatment on bone repair, although incomplete glycemic control could also account for their findings . Considering the longevity of this drug class, it is reasonable to assume that post‐marketing surveillance would identify a serious musculoskeletal safety concern, although teasing out a class‐specific contribution from these drugs could be difficult, considering that they are used less often and typically only in select multi‐component therapy.…”
Section: Drugs and Bonementioning
confidence: 83%
See 1 more Smart Citation
“…A more recent study utilizing the GK rat model of T2D found that treatment with voglibose, one of the newest α‐GI drugs (approved for use in Asia), was insufficient to reverse the negative effects of diabetes on osteo‐integration of dental implants . From this study, the authors inferred a detrimental effect of α‐GI treatment on bone repair, although incomplete glycemic control could also account for their findings . Considering the longevity of this drug class, it is reasonable to assume that post‐marketing surveillance would identify a serious musculoskeletal safety concern, although teasing out a class‐specific contribution from these drugs could be difficult, considering that they are used less often and typically only in select multi‐component therapy.…”
Section: Drugs and Bonementioning
confidence: 83%
“…Moreover, when similar alpha‐glucosidase inhibitory plant phenol extracts have been investigated in rodent models, we could not identify reports of skeletal toxicity or skeletal malformation in these preclinical studies . A more recent study utilizing the GK rat model of T2D found that treatment with voglibose, one of the newest α‐GI drugs (approved for use in Asia), was insufficient to reverse the negative effects of diabetes on osteo‐integration of dental implants . From this study, the authors inferred a detrimental effect of α‐GI treatment on bone repair, although incomplete glycemic control could also account for their findings .…”
Section: Drugs and Bonementioning
confidence: 89%
“…1, 2 The successful healing of bone grafts in these sites of implantation is based on the supply of oxygen and nutrients to the grafted tissue. In non-vascularized bone grafts, revascularization originating from the recipient site is the key process for bone graft survival and successful repair.…”
Section: Introductionmentioning
confidence: 99%
“…To create a clinically compatible rat model for implantation, we have done a comprehensive literature review of rat dental implant models. Implants placed out of oral cavity such as the femur [9][10][11] and the tibia [12,13], or not on the ridge of alveolar bone, i.e., the ramus of mandibular [14] is not considered in the present experiment Fig. 1 a) Time course of the experiment.…”
Section: Introductionmentioning
confidence: 99%